Testing distributed embedded systems through logic analyzer - Kilaru, Chaitanya; JKR Sastry, Dr; K RajaSekhara Rao, Dr (International Journal of Engineering and Technology, 2018)
Testing distributed embedded systems is complex as the individual systems connected on to the network are heterogeneous in nature.The communication system that is used for establishing the networking also varies greatly leading to different testing requirements. Testing of embedded systems can be carried using different methods that include Scaffolding, assert macros, instruction set simulators. In-circuit emulators, logic analyzers each requiring establishment of different testing environment required for undertaking actual testing. Testing of any embedded systems involves testing hardware, testing hardware dependent code, and testing hardware independent code. Logic analyzers are generally used for testing proper working of the Hardware.In this paper, a framework is presented using which testing of hardware distributed across the distributed embedded system using logic analyzer is presented.